Persepsi Pensyarah Matrikulasi terhadap Keperluan Program Peningkatan Profesionalisme - Hafliza, Halili (2004)
The research is aimed to determine the importance of professional development programmes among lecturers of matriculation colleges. 46 correspondents from both genders are chosen from the Northern Zone matriculation colleges. This research has indicated that professional development programmes are vital for lecturers to convey their knowledge to matriculation students. By getting involved in these development programmes, the lecturers will be able to enhance their expertise as well as professionalism. In this research, Pearson Corelation Test and T-Test were used to analyse all the data. Pearson Corelation Test has indicated the close relationship between the statistics obtained and the needs of the professional development programmes for matriculation lecturers. The study involving the research subjects and the data collected from this research complimented each other in terms of results. Finally, some recommendations are put forth to the administrators to improve the professional development programmes at Matriculation Colleges.